ShapeGuide: Shape-Based 3D Interaction for Parameter Modification of Native CAD Data - Okuya, Yujiro; Ladeveze, Nicolas; Fleury, Cédric; Bourdot, Patrick (Frontiers in Robotics and AI, 2018)
While Virtual Reality (VR) technologies are commonly used in industrial companies, loading and modifying CAD parts of commercial CAD systems in virtual environments are still challenging. A few VR applications for Computer Aided Design (CAD) enable users to modify native CAD data in an immersive environment. Even if such VR-CAD applications use 3D interaction space, interaction with parameter values of CAD parts could be enhanced. This paper presents ShapeGuide, a technique allowing users to modify native CAD parts using a shape-based 3D interaction technique. With ShapeGuide, users can achieve modification of parameter values by directly pushing or pulling the surface of a CAD object. In addition, force feedback can be integrated into the technique to enhance the precision of the users' hand motions in the 3D space. In a controlled experiment, we compared ShapeGuide to a standard one-dimensional scroll technique to measure its added value for parametric CAD data modification on a simple industrial product example with an adjusted modification capability. We also evaluated the effect of force feedback assistance on both techniques. Results of this experiment demonstrate that ShapeGuide is significantly faster and more efficient than the scroll technique. Furthermore, they show that the force feedback assistance enhances the precision of both techniques, especially of ShapeGuide.